1986
DOI: 10.1007/bf03010904
|View full text |Cite
|
Sign up to set email alerts
|

A survey of 112,000 anaesthetics at one teaching hospital (1975–83)

Abstract: This paper describes the outcome of a nine-year post-anaesthetic followup program in a large teaching hospital (N = 112,721 anaesthetics). Between time periods 1975-78 and 1979-83, more seriously ill patients (higher ASA physical status) were being treated. Anaesthetic practice also changed, with an increased use of balanced (multiple drug) anaesthetic procedures, a decrease in the use of halothane and an increase in the use of monitoring. Nonfatal anaesthetic compl&ationsintraoperative, recovery room and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
1
16

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(93 citation statements)
references
References 10 publications
10
66
1
16
Order By: Relevance
“…10,19,20,37 Cohen and coworkers found that, even with the same recording system, comparisons between hospitals were difficult. 6 However, for departmental use, the frequency and pattern of problems may be useful indicators of quality.…”
Section: Quality Issuesmentioning
confidence: 99%
“…10,19,20,37 Cohen and coworkers found that, even with the same recording system, comparisons between hospitals were difficult. 6 However, for departmental use, the frequency and pattern of problems may be useful indicators of quality.…”
Section: Quality Issuesmentioning
confidence: 99%
“…Of the general anesthesia errors two occurred during preparation for anesthesia, 39 during induction, nine during maintenance, and six during emergence. Fifty-six of the drug errors occurred during the day (08-16), six during the evening (16)(17)(18)(19)(20)(21)(22)(23)(24), and one during the night (00-08).…”
Section: Incidencementioning
confidence: 99%
“…These 27 cases of aspiration, of which 13 occurred during the postanaesthetic period, led to four deaths and left two patients comatose. In Canada, Cohen et al 13 reported 34 and 38 cases of aspiration of gastric contents in a study of 112,721 anaesthetics during the periods extending from 1975 to 1978 and from 1979 to 1983 respectively, a mean stable incidence of 6.4/10,000. In Sweden, Olsson et ai.…”
Section: Incidence and Clinical Significancementioning
confidence: 99%